2004
DOI: 10.1111/j.1460-9568.2004.03597.x
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of enriched environment on adolescent rats from stressed pregnancies

Abstract: The capacity of an early environmental intervention to normalize the behavioural and immunological dysfunctions produced by a stressed pregnancy was investigated. Pregnant Sprague-Dawley rats underwent three 45-min sessions per day of prenatal restraint stress (PS) on gestation days 11-21, and their offspring were assigned to either an enriched-environment or standard living cages throughout adolescence [postnatal days (pnd) 22-43]. Juvenile rats from stressed pregnancies had a prominent depression of affiliat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
99
0
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 144 publications
(112 citation statements)
references
References 87 publications
8
99
0
5
Order By: Relevance
“…No other sex or pretreatment differences were observed at other time points (e.g., P70, P400, P600), although previous studies have shown decreased anxiety in P600 males prenatally exposed to acute LPS (Golan et al, 2005(Golan et al, , 2006. Compared to prenatal immune activation by pathogens, other forms of prenatal stressors (such as restraint stress) seem to consistently produce anxiety-like behaviors in both prenatally stressed offspring compared to non-stressed control (Kohman et al, 2008a;Laviola et al, 2004).…”
Section: Innate Anxiety-related Behaviorsmentioning
confidence: 56%
“…No other sex or pretreatment differences were observed at other time points (e.g., P70, P400, P600), although previous studies have shown decreased anxiety in P600 males prenatally exposed to acute LPS (Golan et al, 2005(Golan et al, , 2006. Compared to prenatal immune activation by pathogens, other forms of prenatal stressors (such as restraint stress) seem to consistently produce anxiety-like behaviors in both prenatally stressed offspring compared to non-stressed control (Kohman et al, 2008a;Laviola et al, 2004).…”
Section: Innate Anxiety-related Behaviorsmentioning
confidence: 56%
“…That is, the dramatic changes in physiology and neurobehavioral function during adolescence may make an individual extremely susceptible to perturbations (Andersen, 2003;Dahl, 2004), but these striking transitions may also afford an important opportunity to intervene and combat these perturbations. There does appear to be experimental support for this assertion such that exposure to an enriching environment during adolescence can offset many of the negative neurobehavioral and physiological consequences of early life adversity (Bredy, Humpartzoomian, Cain, & Meaney, 2003;Bredy, Zhang, Grant, Diorio, & Meaney, 2004;Francis, Diorio, Plotsky, & Meaney, 2002;Laviola et al, 2004;Morley-Fletcher, Rea, Maccari, & Laviola, 2003), including brain damage (Twiggs, Popolow, & Gerall, 1978). Though it remains to be established whether it is necessary for these interventions to occur during adolescence to be most effective, these data do suggest that a window of opportunity exists for interventions during this crucial period of development.…”
Section: Adolescence: a Perfect Time For Intervetion?mentioning
confidence: 99%
“…There is consolidated evidence to show that the characteristics of the housing environment have a marked influence on the behaviour and welfare of animals, both those raised for biomedical investigation or farm animals (Beattie et al, 2000;Olsen et al, 2002;Laviola et al, 2004;Dong et al, 2007;Brenes et al, 2008). In particular, the provision of straw seems to represent a suitable strategy to alleviate the presence of injurious behaviours in swine (Petersen et al, 1995;Kelly et al, 2000;Guy et al, 2002;Van de Weerd et al, 2006;Studnitz et al, 2007).…”
Section: Introductionmentioning
confidence: 99%